Sylvio [videorecording (Blu-Ray)] - Birney, Albert; Audley, Kentucker; Bernardi, Sylvio; Medel, Tallie; Doherty, Meghan (Music Box Films, 2022)
Based on a series of avant-garde vines by creator Albert Birney, Sylvio is the story of Baltimore-based gorilla Sylvio Bernardi's rise and fall from local TV fame.